HUBUNGAN ANTARA MODAL VENTURA, PASAR PERDANA, DAN PERTUMBUHAN PENDANAAN EKSTERNAL DI PASAR MODAL INDONESIA - Reska Putri Praslita; Audrey Anya Qanitah; Najwa Safira Ramadhani; Zafira Ananda (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the effect of venture capital and the primary market on the growth of external financing among companies in Indonesia. The research background highlights the increasing need for firms to strengthen their capital structure through venture investment support and public market access. A quantitative approach was employed using multiple linear regression to examine the relationship among variables. The sample was selected using purposive sampling, involving companies that received venture capital and/or conducted an IPO. The findings indicate that both venture capital and the primary market have a significant influence on external financing growth, with the primary market exerting the strongest effect. These results confirm that the integration of venture funding and IPO mechanisms plays an essential role in enhancing corporate financing capacity, particularly for expanding businesses in Indonesia.